A novel characterization based framework to incorporate industrial energy management services. (1st May 2022) - Monjurul Hasan, A S M; Trianni, Andrea; Shukla, Nagesh; Katic, Mile
Highlights: A novel framework characterizing industrial energy management services is proposed. Impact of energy management services on production resources & operational productivity are showed. Supports industrial decision makers to assess industrial energy management services. Framework has been empirically validated with experts and applied in industry. Abstract: Energy management has been widely considered as an effective means for achieving energy efficiency and sustainable competitiveness in industrial organizations. However, several barriers prevent its diffused implementation. It is thus crucial to assess and evaluate energy management and the corresponding services in the industrial context in order to further promote them. Extent literature has neither defined industrial energy management services adequately, nor developed any models that consider the characterization of energy management services to support industrial decision making. In light of this, our study aims to provide a comprehensive framework to help key industrial decision-makers and policymakers in making better informed decisions regarding the adoption of energy management activities. We accomplish this by explicitly taking into consideration the characteristics of energy management services based on 25 attributes belonging to four categories i.e., implementation, impacted area, impact on production resources and productivity. In addition, we shed further light on the practical implementation of energy management activities by also placing focus on the link between the implications of their adoption on production resources and the subsequent impact on industrial operations. The framework is validated by a sample of selected energy management experts within Australian organizations, followed by an application in an industrial context. The study concludes with suggestions for industrial decision makers and an outlook on further research avenues.